Studies of multiparticle photonuclear reactions in natural iron induced by 2.5 GeV bremsstrahlung - Pham , Duc Khue; Kim , Tien Thanh; Nguyen , Thi Hien (Nuclear Science and Technology, 2013)
Multiparticle photonuclear reactions produced on natural iron target with maximum end-point energy of 2.5 GeV bremsstrahlung have been investigated by using the activation method in combination with g-ray spectrometric techniques. The g-spectra were measured with a high energy resolution g-spectrometer based on HPGe detector. The radioactive residual nuclei formed via nuclear reactions were identified based on their half-lives and g-ray energies. The yields of reaction products were determined based on their g-activities. In order to improve the accuracy of the experimental results a series of g-spectra were measured at different cooling times and the necessary corrections were made. More than twenties radioactive nuclei formed via the following photonuclear reactions: natFe(g,xn), natFe(g,xnyp) and natFe(g,p-xn) have been identified and their yields have been determined. The present experimental results are compared with reference data and analyzed with an empirical formula given by Rudstam.